Effects of pulse duration on muscle fatigue during electrical stimulation inducing moderate‐level contraction. Issue 4 (13th September 2017) - Jeon, Woohyoung; Griffin, Lisa
ABSTRACT: Introduction : Neuromuscular electrical stimulation (NMES) is used to prevent muscle atrophy. However, the effect of pulse duration modulation for reducing muscle fatigue and pain is unknown. Methods : Two 2‐minute stimulation protocols were applied to the knee extensors of 10 healthy individuals. In 1 session, a long pulse duration (1, 000 μs) and a low current amplitude (LL), set to evoke 25% maximal voluntary contraction at 30 Hz, were applied. The other session was identical except that a short pulse duration (200 μs) and a high current amplitude (SH) were used. Results: Muscle fatigue was lower for LL than for SH ( P < 0.01). Force recovery rate was higher for LL than for SH ( P < 0.05). Pain scores were also lower for LL than for SH ( P < 0.05). Discussion: The use of 1‐ms pulse durations reduces fatigue and pain during NMES for moderate‐level contractions compared with 200‐μs durations. Muscle Nerve 57 : 642–649, 2018